The role of aquaria in the advancement of elasmobranch reproductive biology - Feldheim, Kevin A.; Wyffels, Jennifer T.; Lyons, Kady (Frontiers in Marine Science, 2022)
Public aquaria showcase aquatic life while raising awareness and educating the public on biodiversity and the need for conservation. Recently, aquaria have followed in the footsteps of zoos by taking more directed approaches in species conservation as well as leveraging animals in their collection to fill biological knowledge gaps through research. Similar to zoos, aquaria are able to house animals that are not feasible to care for in traditional academic settings, allowing important life history information to be gained. In particular, our understanding of reproductive aspects of large migratory fishes such as elasmobranchs (sharks, skates and rays) have benefited from information gleaned in aquarium settings that would otherwise be difficult or impossible to study in the natural environment. For example, the ability of elasmobranchs to reproduce parthenogenetically was discovered through observation of sharks maintained in public aquaria. Since its discovery, parthenogenesis has been observed for many ex situ shark and ray species. Aquaria have made other important contributions to characterizing elasmobranch reproductive biology such as understanding reproductive cycling and trialing assisted reproductive techniques, among others. Here, we review the role aquaria have played in the field of elasmobranch reproductive biology and discuss how zoos and aquariums can continue to contribute to this field in the future.